Monitoring Patient Safety in Real-Time - An Application of Design and Systems Thinking - Moogi, Vishwal (My University, 2021)
The thought of being hospitalized always strikes a fear in the mind of an individual. According to the Swedish Board of Health and Welfare, nearly 10 percent of the patients administered into healthcare fall victim to adverse events that emerge from patient safety risks. Patient safety within the healthcare context has been gaining increased attention and providing quality care to the patients has become a top priority. Therefore, monitoring patient safety in real-time is the need of the hour. The purpose of the thesis is to develop customer-focused solutions for online monitoring of patient safety in real-time using design and systems thinking approach. The design thinking approach benefits in developing customer-centric solutions; it offers a framework entailing empathy building, radical collaboration and prototyping to manage healthcare and innovation. The healthcare is a complex system consisting of various components that interact with each other across different system levels and interfaces, hence a systems safety approach is beneficial in this context. It is especially useful to monitor patient safety as healthcare systems are often subject to change and are highly unpredictable. The findings on existing ways of monitoring and managing patient safety uncovers several pain points and user needs to which a solution is proposed. A multi-tab dashboard that displays key metrics and data associated with managing patient safety is developed. A medium-fidelity prototype was generated through multiple rapid iterations and recommendations for full scale dashboard have been provided. This solution will help in establishing a systems perspective on safety in managing and monitoring patient safety at the healthcare facility.